Is two-tier health care the future? - Flood, Colleen M.; Thomas, Bryan, 1973- (Law, technology, and media., 2020)
"Canadians are deeply worried about wait times for health and this book explores whether or not two-tier health care is a solution. Entrepreneurial doctors and private clinics are bringing Charter challenges to existing laws restrictive of a two-tier system. They argue (wrongly in our view) that Canada is an outlier amongst developed countries in limiting options to jump the queue. In this book, leading researchers explore the public and private mix in Canada and within countries such as Australia, Germany, France and Ireland. We explain the history and complexity of interactions between public and private funding of health care. We also explain the many regulations and policies found in different countries used to both inhibit and sometimes to encourage two-tier care (for example, tax breaks). If a Canadian court strikes down laws restrictive of two-tier, Canadian governments can (i) permit and even encourage two-tier care to grow; (ii) pass new regulations that allow a small measure of two-tier care; or (iii) take positive steps to eliminate wait times in Canadian health care, and thereby reduce demand for two-tier care. We argue for option three as the best means to ensure Canadian principles of equity in access, ensure timely care, and fend off constitutional challenges. This work is critical not only for court challenges but also for Canadian governments who need the best evidence possible about different approaches to regulating two-tier care if they are forced by a court to revisit existing laws as a result of a successful Charter challenge."--